Natural Antioxidant Potential of Cassia siamea Flowers: Influence of Solvents on Phytochemicals and Activity - jusman jusman; Syamsuddin Syamsuddin (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
This study meticulously investigates the pivotal influence of solvent polarity on the phytochemical profile and antioxidant efficacy derived from Cassia siamea flower extracts. Employing three solvents across a polarity gradient n-hexane (non-polar), ethyl acetate (semi-polar), and ethanol (polar) the extracts were rigorously evaluated via qualitative phytochemical screening and antioxidant capacity determination using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. Phytochemical richness was quantified based on the presence thresholds of alkaloids, flavonoids, tannins, and saponins, while antioxidant potential was established through IC50​ value calculations. Remarkably, the results unveiled a strong, direct correlation underpinning solvent polarity, phytochemical yield, and measurable bioactivity. The ethanol extract decisively exhibited the highest phytochemical richness and the most potent radical-scavenging activity, yielding an IC50​ of 18.43 ppm, significantly outperforming ethyl acetate (39.87 ppm) and n-hexane (70.12 ppm). Supporting this evidence, visual analysis utilizing heatmaps, scatter plots, and dual-axis charts further substantiated the pronounced inverse relationship between phytochemical richness and IC50​ values. These compelling findings confirm that more polar solvents are inherently superior for extracting critical antioxidant-active compounds, particularly flavonoids and phenolics. Consequently, ethanol stands out as the optimal solvent for maximizing both chemical diversity and biological efficacy. This research contributes substantial insights for refining extraction methodologies. It robustly supports the application of ethanol-based extracts in developing high-value antioxidant formulations across the pharmaceutical, nutraceutical, and cosmeceutical sectors